Features of tensoresistance in single crystals of germanium and silicon with different dopants - Baranskii, P.I.; Gaidar, G.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Tensoresistance in single crystals of germanium and silicon with different dopants but under practically equal charge carrier concentrations have been investigated. The features of ρX /ρ₀ = f(X) function, which depend on individual physical-chemical properties of dopants, have been discussed in this paper.